Proceedings of the 31st Annual ACM Symposium on Applied Computing 2016
DOI: 10.1145/2851613.2853124
|View full text |Cite
|
Sign up to set email alerts
|

Sensor network based solar forecasting using a local vector autoregressive ridge framework

Abstract: The significant improvements and falling costs of photovoltaic (PV) technology make solar energy a promising resource, yet the cloud induced variability of surface solar irradiance inhibits its effective use in grid-tied PV generation. Short-term irradiance forecasting, especially on the minute scale, is critically important for grid system stability and auxiliary power source management. Compared to the trending sky imaging devices, irradiance sensors are inexpensive and easy to deploy but related forecasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Satellite images predict the clouds movement over a broad region for a time period ranging from 0.5 h to 6 h. These images are mainly used for forecasting cloud movements of huge and slow‐moving clouds [28, 29, 68, 69]. Irradiance sensors are cost‐effective and easily employable when compared to the famous sky imaging devices [70]. Geographically distributed sensor networks with a dense arrangement of sensors and permanent measurement of output power are good enough to provide input data for short‐term CMVs with acceptable accuracy [4, 71].…”
Section: Methods For Solar Irradiance Forecastingmentioning
confidence: 99%
“…Satellite images predict the clouds movement over a broad region for a time period ranging from 0.5 h to 6 h. These images are mainly used for forecasting cloud movements of huge and slow‐moving clouds [28, 29, 68, 69]. Irradiance sensors are cost‐effective and easily employable when compared to the famous sky imaging devices [70]. Geographically distributed sensor networks with a dense arrangement of sensors and permanent measurement of output power are good enough to provide input data for short‐term CMVs with acceptable accuracy [4, 71].…”
Section: Methods For Solar Irradiance Forecastingmentioning
confidence: 99%
“…While Sensor Networks often span over several hundred meters [19] or even kilometers [20], research on the use of low-cost illuminance meters showed that small networks can also detect cloud shadow movement when the sampling rate is high enough. Espinosa-Gavira et al [21] used a network of 16 lux meters, spanning only 15 m by 15 m, that was able to detect cloud shadow movement.…”
Section: Sensor Networkmentioning
confidence: 99%
“…Most recently, several studies have proposed data-driven forecast methods that use multi-site spatio-temporal historical data for PV forecasting without requiring NWP or cloud movement information [11][12][13][14][15][16][17][18][19]. Simple and fast multi-site forecasting techniques using linear autoregressive (AR) models are proposed in [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, several studies have proposed data-driven forecast methods that use multi-site spatio-temporal historical data for PV forecasting without requiring NWP or cloud movement information [11][12][13][14][15][16][17][18][19]. Simple and fast multi-site forecasting techniques using linear autoregressive (AR) models are proposed in [11][12][13]. The work in [12] proposes a lasso regularization in the AR model to automatically select the input variables, while the work in [13] further develops the AR model into a local vector AR model with ridge regularization that considers local weather changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation